Early functional changes in lewy body dementia: roles of dynamics, locus coeruleus, and compensation - Kristína Mitterová; Eva Výtvarová; Anežka Kovářová; Martin Lamoš; Jan Fousek; Irena Rektorová (Alzheimer’s Research & Therapy)
Abstract Dementia with Lewy bodies (DLB) is marked by multidomain cognitive impairments, with fluctuations in cognition and alertness being among the most common clinical features. Disruptions in functional connectivity are thought to underlie these fluctuations, but it remains unclear whether such patterns are already present at prodromal stages. We investigated the presence of static and dynamic functional connectivity alterations and their contribution to the clinical phenotype of prodromal DLB, and explored their association with declining locus coeruleus integrity, while considering premorbid intelligence (a proxy for cognitive reserve) as a moderating factor. Three groups of participants on the prodromal spectrum were analyzed: 29 healthy controls, 58 cognitively normal subjects with core clinical features of prodromal DLB (CN-CCF), and 39 subjects with mild cognitive impairment due to Lewy body dementia (MCI-LB). Dynamic and static functional connectivity features were derived from resting-state source-reconstructed high-density EEG, and integrity of the right caudal locus coeruleus was quantified using neuromelanin-sensitive MRI. Robust analyses, such as PERMANOVA, Spearman correlations and general linear models were conducted to study the relationships. We observed a nonlinear trajectory of two functional connectivity metrics—temporal variability (fluidity) and connectedness (average node strength)—across symptom severity, especially in the delta frequency band. Both measures (F(2,123) = 1.86, p =.037; F(2,123) = 1.51, p =.023, respectively) were elevated in the intermediate severity groups—that is, in CN-CCF and possible MCI-LB (i.e., one core clinical feature)—and this was associated with better executive functioning after controlling for age and premorbid intelligence (rho = 0.26, p =.004; rho = 0.28, p =.002, respectively). Additionally, elevated fluidity (rho = − 0.34, p =.034) and average node strength (rho = − 0.37, p =.022) were also correlated with fewer fluctuations in alertness in subjects with MCI-LB. Fluidity was further associated with right caudal locus coeruleus integrity, particularly among individuals with lower premorbid intelligence (F(5,97) = 3.56, p =.005). Our findings indicate that increased dynamic reconfiguration and enhanced connectivity may serve compensatory functions in early DLB, helping temporarily preserve cognition. As DLB progresses, these mechanisms wane, with noradrenergic contributions more evident in individuals with lower cognitive reserve. Clinical trial number Not applicable.